The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1002/da.22116
|View full text |Cite
|
Sign up to set email alerts
|

Role of Maternal Childhood Trauma on Parenting Among Depressed Mothers of Psychiatrically Ill Children

Abstract: Background Independently, maternal depression and maternal history of childhood abuse confer risk for impaired parenting. These associations may be compounded when depressed mothers with histories of childhood abuse are faced with the challenge of parenting offspring who themselves struggle with mental health problems. This study examined the relationships among maternal history of childhood abuse, maternal depression, and parenting style in the context of parenting a psychiatrically ill child, with an emphasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 49 publications
3
24
1
Order By: Relevance
“…Seven studies explored the impact of mothers' emotionally abusive and neglectful childhood experiences on the way in which they related to their children, using measures of parenting stress (Lang et al ., ; Pereira et al ., ), prenatal attachment (Siddiqui et al ., ), acceptance and psychological control (Zalewski et al ., ), maternal representations of the infant (Malone et al ., ), perceptions of infant behaviour (Lang et al ., ), parenting style (Bert et al ., 1999), maternal sensitivity (Pereira et al ., ) and engagement with play/praise (Fujiwara et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies explored the impact of mothers' emotionally abusive and neglectful childhood experiences on the way in which they related to their children, using measures of parenting stress (Lang et al ., ; Pereira et al ., ), prenatal attachment (Siddiqui et al ., ), acceptance and psychological control (Zalewski et al ., ), maternal representations of the infant (Malone et al ., ), perceptions of infant behaviour (Lang et al ., ), parenting style (Bert et al ., 1999), maternal sensitivity (Pereira et al ., ) and engagement with play/praise (Fujiwara et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Zalewski et al . () found that mothers who self‐reported childhood emotional abuse were rated by their children as being significantly lower in acceptance and higher in psychological control. This relationship was independent of maternal depression and other parental risk factors (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptual models (Hammen et al, 2004) and empirical findings from behavioral studies (Lovejoy et al, 2000) suggest that one putative mechanism for disease transmission across generations is maladaptive parent-child relationships in dyads with a depressed parent. Altered responses to child affect and maladaptive relationship patterns may be especially apparent in depressed mothers with psychiatrically ill children (Zalewski et al, 2013). Specifically, maternal neural function in emotional processing circuits is altered in depression (Barrett and Fleming, 2011) and may be associated with disruptions in parent-child relationships previously observed in depressed mother-child dyads.…”
Section: Introductionmentioning
confidence: 99%
“…Parental capacity to enjoy the rewarding aspects and manage the difficult aspects of parenting may be attenuated by parental depression (Zalewski et al, 2013). Depressed individuals show blunted ventral striatal (VS) activation in response to positive stimuli (Zhang et al, 2013), suggesting diminished pleasure in response to reward, and heightened response in the amygdala and insula to negative stimuli (Hamilton et al, 2012), indicating heightened negative affect in response to threatening stimuli.…”
Section: Introductionmentioning
confidence: 99%